2015
DOI: 10.1017/jfm.2015.113
|View full text |Cite
|
Sign up to set email alerts
|

Joint probabilities and mixing of isolated scalars emitted from parallel jets

Abstract: Mixing and reaction between two scalars initially separated by scalar-free ambient fluid is important in problems ranging from ecology to engineering. Using a two-channel planar laser-induced fluorescence (PLIF) system the instantaneous spatial structure of two independent scalars emitted from parallel jets into a slow coflow is quantified. Of particular interest is the scalar covariance used to define the correlation coefficient. Joint probability distribution functions (JPDFs) and instantaneous images of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…Segregating an unknown odorant from a mixture is a blind source separation problem, and solving it requires more information than just the chemical odorant identity (Hendin et al, 1994). The physics of odorant dispersion adds relational information to the chemical odorant identity, as odorants from the same source form plumes with relatively stable odorant concentration proportions (homogeneous plumes), while odorants from different sources form plumes with variable odorant concentration proportions (heterogeneous plumes; Hopfield, 1991; Kree et al, 2013; Celani et al, 2014; Riffell et al, 2014; Soltys and Crimaldi, 2015; Erskine et al, 2019). Indeed, animals can use these relational stimuli to detect whether odorants originate from the same or different sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Segregating an unknown odorant from a mixture is a blind source separation problem, and solving it requires more information than just the chemical odorant identity (Hendin et al, 1994). The physics of odorant dispersion adds relational information to the chemical odorant identity, as odorants from the same source form plumes with relatively stable odorant concentration proportions (homogeneous plumes), while odorants from different sources form plumes with variable odorant concentration proportions (heterogeneous plumes; Hopfield, 1991; Kree et al, 2013; Celani et al, 2014; Riffell et al, 2014; Soltys and Crimaldi, 2015; Erskine et al, 2019). Indeed, animals can use these relational stimuli to detect whether odorants originate from the same or different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Natural olfactory stimuli are typically mixtures of many different odorants from different sources, which mix together in turbulent plumes (Murlis et al, 1992; Kree et al, 2013; Celani et al, 2014; Riffell et al, 2014; Soltys and Crimaldi, 2015; Erskine et al, 2019). Previous studies suggested that animals perceive odorant mixtures synthetically, that is, they perceive a mixture as a perceptual unit rather than as a list of individual odorants (humans: Jinks and Laing, 1999; squirrel monkeys: Laska and Hudson, 1993; rats: Staubli et al, 1987; spiny lobsters: Lynn et al, 1994, honey bees: Chandra and Smith, 1998; Smith, 1998; Deisig et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
and experimentally (Soltys and Crimaldi 2015). This scalar coalescence occurs even for passive scalars where the dynamics of each scalar field evolves independently of the other; the structure of the shared velocity field is responsible for the coalescence.
…”
mentioning
confidence: 90%
“…Both numerical 14,15 and experimental 16 studies have shown that the stirring of initially distant scalars may result in their eventual overlap. When the concentration of the filaments is not too low, these coalescence events have been shown to lead to reaction rates much greater than would be predicted by a well-mixed system, a process that we refer to as reaction enhancement.…”
Section: A Enhanced Reaction Of Initially Distant Scalarsmentioning
confidence: 99%